Development of Primary Care Research in North America, Europe, and Australia From 1974 to 2017 - Hajjar, Florence; Saint-Lary, Olivier; Cadwallader, Jean-Sébastien; Chauvin, Pierre; Boutet, Alexandre; Steinecker, Magali; Robert, Sarah; Ibanez, Gladys (Annals of family medicine, 2019)
Research is a necessity for high-quality medicine. We used the MEDLINE database to conduct a bibliometric analysis of research output with respect to primary care by 21 countries. For the period 1974 to 2017, the United States and the United Kingdom stood out in terms of publication volume, and the UK, Canada, and Australia had the greatest percentage of publications in primary care. As of 2017, publications in primary care represented a small proportion of total publications. The countries with the greatest publication productivity possess factors that should be considered with respect to strengthening research in primary care.